ANALISIS KOMPARASI DAYA SAING EKSPOR TEKSTIL DAN PRODUK TEKSTIL INDONESIA-VIETNAM TERHADAP PASAR AMERIKA SERIKAT TAHUN 2010-2014 - Nofi Ika Nurizza; Firman Rosjadi Djoemadi; Idfi Setyaningrum (CALYPTRA, 2018)
This study aims to compare the competitiveness of Indonesian textile and textile product exports with Vietnam to the US market in the period 2010- 2014, which in 2012 economic crisis occurred. The object used in this study is the value of Reveald Comparative Advantage (RCA) Indonesia and Vietnam with a period of five years. Comparison in this analysis using comparative research with descriptive methods. The results show that Indonesia's competitiveness is strong in the US market because the value is more than one but the value is still far below Vietnam. The t-test shows a significant difference in the value of RCA and ISP Indonesia-Vietnam within five years. This is indicated as the impact of the economic crisis in 2012. There are factors that affect the competitiveness of Indonesian exports. These factors tend to be an obstacle for increasing the competitiveness of Textileand Textile Products to international markets, especially the United States.